Development of an indoor air quality (IAQ) standard for extended work shifts on Royal Malaysian Navy (RMN) ships - Zahaba, Maryam; Romali, Siti Hajar Najihah; Tamsi, Nur Sarah Fatihah; Kamaruddin, Amirul Faiz; Nik Yusof, Nik Nur Auni; Ramli, Muhammad Zaki; Hassan, Noor Artika; Omar, Mohd Norhisyam; Ariffin, Arman; Abdullah, Mohd Shaiful Adli Chung (Science & Technology Research Institute for Defence (STRIDE), Ministry of Defence Malaysia, 2026)
Indoor air quality (IAQ) in shipboard environments is often compromised by confined spaces, limited ventilation, and exhaust gas infiltration. This condition poses health concerns for Royal Malaysian Navy (RMN) crews who spend extended period onboard. Yet, there are still no established IAQ standards that can be referred to, not only in naval settings but also across the global maritime industry, for protecting the health of the crews. Therefore, this study was proposed to develop an IAQ standard for Royal Malaysian Navy (RMN) ship, namely the RMN IAQ Standard 2025. The standard development process involved six phases, which began with in-depth interviews with experts to gain insights into the development. Relevant data was collected from a wide range of sources, such as IAQ standards for building settings, ambient standards, ship standards and personal exposure standards for reference purposes. The data was continuously analysed for refinement through data extraction, cleaning and classification. The development continued with the selection of established adjustment models to determine the extended working hours exposure limit for the ship crew onboard. Following the selection, the adjustment calculation was performed for the new value of the adjusted 12 h time weighted average (TWA12) using the formula of the selected adjustment model. Finally, the standard development was finalised with the establishment of the RMN IAQ Standard 2025, which compiles the adopted and adjusted new values of the IAQ parameters. The adjustment of chemical parameters adapted the Quebec model, while the standard limits for both physical and biological parameters were adopted from established reference standards to suit the RMN ship operation. As a result, the standard limits were set for physical, chemical and biological parameters. In conclusion, an IAQ standard for shipboard environments was established through the development of the RMN IAQ Standard 2025, marking an important step toward regulating IAQ in maritime settings. The standard is designed to protect the health and well-being of RMN personnel and can also be adopted as a guideline for other vessels within the maritime industry.